(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2024)
In light of recent events surrounding higher education, colleges and universities around the country are coming under fire for their handling of addressing current events. In an effort to combat this, Vanderbilt has adopted a policy of "principled neutrality"—a policy that has not been well received by many. In this paper, I provide reasoning for why it is our best course of action, not just for the university, but for every student and faculty member as well. For additional context, listen to the author’s reflection on the piece below.